Um estudo do conhecimento histórico das formas de atendimento socioassistencial e da proposição/implantação do Creas/média complexidade no município de São Paulo: uma questão em análise 1940/2011 - Cordeiro, Tiago Gomes (2011)
The current dessertation aims to a study of historical knowledge of the main forms of social assistance services in São Paulo, in the period 1940-2004 and knowledge in the proposition/deployment of Creas/medium complexity, in the context of the PNAS/Suas, in the period 2004-2011. The overall objective was to identify and analyze the historical knowledge of the forms of social assistance services in São Paulo, from 1940-2004, was considered in the proposition/deployment of Creas/medium complexity, in the context of PNAS/Suas, in the period of 2004-2011, in view of its inclusion in the historical processual social assistance. Formulated as guiding question: What perceptions that the research subjects have the historical knowledge of the forms of social service assistance and knowledge of the proposition/deployment of Creas/medium complexity and integration of knowledge in historical processual social care in São Paulo? The main conceptual frameworks were: Poverty, Social Vulnerability and Social Risk; Social Policy, Social Law and Social Protection; PNAS, SUAS and Creas/medium complexity, based on contemporary works and authors of Social Work and Sociology. The methodology focused on qualitative research, comprising research literature, documentary research and field research, beyond the observation of the dynamics of operation of the studied Creas units. The five subjects were: Two faculty/academic researches from PUC/SP, two social workers/unit managers Creas and a social worker/technician Smads. Content analysis was adopted for the interpretation of the meanings of the data collected. The results indicate that the subjects do not consider the inclusion of the proposition/deployment of Creas/medium complexity in the extend of processivity historic welfare in São Paulo, that is 1940-2011